2009
DOI: 10.1177/00333549091244s105
|View full text |Cite
|
Sign up to set email alerts
|

Ethnographic Evaluation of a Lay Health Promoter Program to Reduce Occupational Injuries among Latino Poultry Processing Workers

Abstract: We evaluated a lay health promoter program providing occupational health and safety education to immigrant Latino poultry processing workers in western North Carolina. While such programs are advocated for addressing the health education deficits of immigrant and disadvantaged populations, their application in occupational health has been limited to farmworkers. A community-university partnership recruited and trained promoters to deliver lessons on musculoskeletal injuries, slips and falls, and workers' right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
(29 reference statements)
2
26
0
1
Order By: Relevance
“…(7982)]. Bush et al (81) piloted a promotoras program with forest workers and found increased knowledge and awareness of OSH risks and resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7982)]. Bush et al (81) piloted a promotoras program with forest workers and found increased knowledge and awareness of OSH risks and resources.…”
Section: Resultsmentioning
confidence: 99%
“…They highlighted the importance of providing non-literacy-based outreach and training tools and leadership development opportunities for promotoras and engaging promotoras in community outreach to connect with workers in comfortable environments (e.g., homes, community festivals, churches). It is also important that promotoras be frequently praised; educated regarding local, state, and national events affecting immigrant workers; supported in troubleshooting personal, community, and work-related obstacles; and provided with an honorarium to make the investment of their time worthwhile and foster a sense of accomplishment (82). The value of adopting participatory approaches, both in terms of training methods and project planning has been emphasized in order to promote effectiveness, commitment, and leadership skills among peer trainers (83).…”
Section: Resultsmentioning
confidence: 99%
“…Over 28 months, five promotoras delivered the lesson to 731 workers. Both ethnographic data [28] and a more formal pre-post evaluation in a small sample of workers [22] demonstrated improvements in knowledge and self-efficacy, and appropriate behavior changes. Based on this success, five other lessons were developed and disseminated into the community using promotoras .…”
Section: Designing a Training Programmentioning
confidence: 99%
“…Qualitative methods can generally be understood as relying on descriptive in-depth information. Qualitative methods allow participants to explain their situation in their own words, which is particularly useful in identifying underlying perspectives, assumptions, and reactions that can be helpful in bridging the cultural gap between trainers and participants of diverse backgrounds [28]. Common examples of qualitative data include open-ended individual interviews, focus groups, and debriefing sessions.…”
Section: Evaluation Of Training and Education Programsmentioning
confidence: 99%
“…Poultry industry companies provide, to workers, limited training on security purposes and the effects of the pace of work on them, so that many do not understand how their activities in the production line are related to the musculoskeletal injuries they acquire [10,11]. Mohamed [12], mentions the importance of more focus on management measures that can align the strategic focus on security for the entire organization, and Kaminski [13] points out that the significant negative relationship between capital intensity and injury rates suggests a relationship between risk controls and injuries.…”
Section: Introductionmentioning
confidence: 99%